The Impact of Providing Chatbot Content on Developing the English Communication Skills among Al-Azhar Kindergarten Teachers - Ahmed Tawfik, Ghada Mohamed (European Scientific Journal, ESJ, 2023)
This research aimed at investigating the impact of using Chatbot content on improving the English communication skills of Al-Azhar Al-Sharif kindergarten teachers. The researcher used a quasi-experimental design to explain the difference occurred in the teachers` performance before and after the intervention of the Chatbot content. This design required the researcher to develop a performance observation checklist; the main tool of this research. In addition, the researcher constructed the Chatbot content; the e-training program. Having the research design completed, thirty-three (33) female Azhari kindergarten teachers participated in this experiment. The performance observation checklist was used for evaluating the teachers` performance before and after the intervention of the Chatbot content, and for measuring the teachers` retention of the acquired skills. At the end of the research, a statistical analysis of the results was applied. The results showed a statistically significant difference at the level of (0.05) on the performance observation checklist`s mean scores of the sample teachers’ pre and post application of the Chatbot content in favor of the post-application. The second statistical analysis of the performance observation checklist showed that there is no significant difference between the sample teachers` mean scores in the post and follow-up application of the Chatbot content. These results proved the validity of the research main assumption that Chatbot content can improve the English communication skills of kindergarten teachers.